Perawatan Pergeseran Mandibula dan Kliking Menggunakan Teknik Edgewise dan Trainer - Utami, Rully; Ardhana, Wayan; Christnawati, Christnawati (Majalah Kedokteran Gigi Indonesia, 2014)
Kasus ini terjadi pada perempuan usia 22 tahun yang bersedia dipublikasikan untuk kepentingan  ilmu pengetahuan. Keluhan utama mandibula dan dagunya bergeser ke kanan, gigitan terbuka posterior dan bunyi click di persendian temporomandibular. Diagnosis pasien adalah maloklusi Angle kelas III tipe dento skeletal, pergeseran garis tengah mandibula dan dagu ke kanan, gigitan terbuka posterior dan clicking pada sendi temporomandibular. Perawatan dilakukan dengan teknik Edgewise dan trainer. Leveling dan unraveling dilakukan menggunakan kawat stainless steel bulat diameter 0,014 mm dengan multiloop. Trainer digunakan untuk koreksi pergeseran mandibula. Perawatan dilakukan selama 11 bulan, dan menunjukkan hasil hubungan molar pertama kanan menjadi kelas I. Overjet meningkat dari 0,1 mm menjadi 2 mm, overbite meningkat dari 0,2 mm menjadi 2,57 mm, garis tengah mandibula yang semula bergeser ke kanan 4,38 mm menjadi 2,53 mm, gigitan terbuka posterior dan clicking telah terkoreksi.ABSTRACT: Compromised Treatment of Class III Malocclusion with Mandibular Shifting, Posterior Openbite and Clicking Using Edgewise Technique and Trainer In Adult. This case report described the treatment of an adult female 22 years old who complained that her mandibula and chin shift to the right, posterior openbite and clicking. The patient diagnosed class III molar relationship, skeletal class III malocclusion, mandibular midline and chin shift to the right, posterior openbite and clicking on temporomandibular joint. Treatment was conducted using combination between  Edgewise Technique and trainer.  Leveling and unraveling are achieved by round stainless steel archwire 0,014 mm with multiloop. Trainer used to corrected the mandibular shifting. Result after 1 years treatment showed that the right molar relationship became class I, overjet increased  from 0,1 mm to 2 mm, overbite increased  from 0,2 mm to 2,57 mm, mandibular midline shifting decresed from 4,38 mm to 2,53 mm,  posterior openbite and clicking have been corrected.